Controlling Intermolecular Interaction and Interphase Chemistry Enabled Sustainable Water‐tolerance LiMn2O4||Li4Ti5O12 Batteries. (4th November 2022) - Li, Qin; Yang, Chongyin; Zhang, Jiaxun; Ji, Xiao; Xu, Jijian; He, Xinzi; Chen, Long; Hou, Singyuk; Uddin, Jasim; Addison, Dan; Sun, Dalin; Wang, Chunsheng; et al.
Abstract: Solid electrolyte interphase (SEI) formation and H2 O activity reduction in Water‐in‐Salt electrolytes (WiSE) with an enlarged stability window of 3.0 V have provided the feasibility of the high‐energy‐density aqueous Li‐ion batteries. Here, we extend the cathodic potential of WiSE by rationally controlling intermolecular interaction and interphase chemistry with the introduction of trimethyl phosphate (TMP) into WiSE. The TMP not merely limits the H2 O activity via the strong interaction between TMP and H2 O but also contributes to the formation of reinforced SEI involving phosphate and LiF by manipulating the Li + solvation structure. Thus, water‐tolerance LiMn2 O4 (LMO)||Li4 Ti5 O12 (LTO) full cell with a P/N ratio of 1.14 can be assembled and achieve a long cycling life of 1000 times with high coulombic efficiency of >99.9 %. This work provides a promising insight into the cost‐effective practical manufacture of LMO||LTO cells without rigorous moisture‐free requirements. Abstract : LiTFSI‐TMP‐H2 O electrolytes with an expanded electrochemical stability window of 3.7 V are rationally designed by controlling intermolecular interaction and interphase chemistry. Benefiting from reduced H2 O activity and reinforced solid electrolyte interphase, the assembled water‐tolerance LiMn2 O4 ||Li4 Ti5 O12 full cell with a limited P/N ratio of 1.14 can achieve a long cycling life with high coulombic efficiency.